2012
DOI: 10.1371/journal.pone.0031629
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of Adult Black Marlin (Istiompax indica) from a Great Barrier Reef Spawning Aggregation

Abstract: The black marlin (Istiompax indica) is one of the largest bony fishes in the world with females capable of reaching a mass of over 700 kg. This highly migratory predator occurs in the tropical regions of the Pacific and Indian Oceans, and is the target of regional recreational and commercial fisheries. Through the sampling of ichthyoplankton and ovaries we provide evidence that the relatively high seasonal abundance of black marlin off the Great Barrier Reef is, in fact, a spawning aggregation. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 12 publications
3
48
0
1
Order By: Relevance
“…Sailfish are among the most surface oriented of the billfishes, spending over 80% of their time at surface temperatures during the day and 93% at night in the Atlantic, which is consistent with the behavior reported for sailfish in the Pacific [63,72,73] and for the only two longbill spearfish that have been tagged [50]. Black marlin in the Coral Sea were found to occupy shallow waters warmer than 24°C [60], and their horizontal movements correlated with the spread of 26°C-27°C sea surface temperatures (SST) [61]. Striped marlin are also largely surface oriented, spending 80% of their time in the mixed layer and 72% in the top 5 m [66].…”
Section: Biophysical Drivers Temperaturesupporting
confidence: 74%
See 2 more Smart Citations
“…Sailfish are among the most surface oriented of the billfishes, spending over 80% of their time at surface temperatures during the day and 93% at night in the Atlantic, which is consistent with the behavior reported for sailfish in the Pacific [63,72,73] and for the only two longbill spearfish that have been tagged [50]. Black marlin in the Coral Sea were found to occupy shallow waters warmer than 24°C [60], and their horizontal movements correlated with the spread of 26°C-27°C sea surface temperatures (SST) [61]. Striped marlin are also largely surface oriented, spending 80% of their time in the mixed layer and 72% in the top 5 m [66].…”
Section: Biophysical Drivers Temperaturesupporting
confidence: 74%
“…Thorough larval collections in the Straits of Florida [81] indicate that spawning activity for the dominant istiophorids in the Atlantic (sailfish and blue and white marlin) generally occurs from April to October, while swordfish larvae have been collected year-round [81,82]. Other collections have identified billfish larvae from Hawaii, Gulf of California, and the Great Barrier Reef [61,[83][84][85], most of which encompassed several months of the year.…”
Section: Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent pop-up satellite archival tagging of adult black marlin off the Great Barrier Reef during the spawning season provided insights on movements of individuals for up to six months following G Model No. of Pages 8 the spawning season and demonstrated that the spawning aggregation has a catchment area that extends up to 5000 km from the spawning area (Domeier and Speare, 2012).…”
Section: Billfish Population Structurementioning
confidence: 99%
“…For example, within the northern region of Australia's Great Barrier Reef Marine Park (GBRMP), a number of "buffer" zones (3% of the entire marine park) exist to allow trollfishing for pelagic species, because this activity is deemed low impact (GBRMP Authority 2003). Buffer zones were introduced in 2004 to protect a historically and socioecologically important sport fishery that targets spawning aggregations of black marlin (Istiompax indica; Domeier and Speare 2012). Unfortunately, marlin catch-and-release fishing may be characterized by unrecorded and cryptic mortality, with anglers in the GBRMP black marlin fishery routinely losing hooked fish to sharks, and fish released in weakened condition are likely to be preyed upon (Domeier et al 2003).…”
Section: Fisheries-related Stressors In the Spanish Flag Snapper (Lutmentioning
confidence: 99%